ANALISIS PROFIL PEMAHAMAN KONSEP PESERTA DIDIK BERDASARKAN REPRESENTASI KIMIA PADA MATERI FAKTOR-FAKTOR YANG MEMPENGARUHI LAJU REAKSI - Alvince Stevani Lase; Try Sepakat Zalukhu (Universitas Samudra, 2026)
Students’ understanding of the factors that influence reaction rates remains challenging due to the abstract nature of the concepts and the cognitive demand of integrating multiple levels of chemical representation. This study aims to map students’ conceptual understanding profiles based on chemical representations in the reaction rate material. The research employed a descriptive method with a quantitative approach involving 64, class XI-1 and XI-2. Data were collected using a four-tier diagnostic test and analyzed based on understanding categories, representational abilities, and subtopics. The results show that only 44.66% of students were in the concept-understanding category, while 20.70% partially understood the concepts, 35.16% did not understand the concepts, and 27.34% exhibited misconceptions. Further analysis revealed that the microscopic representation was the largest source of errors, with 22.40% falling into the non-understanding category and 21.61% into the misconception category. Understanding based on subtopics also varied, with misconceptions reaching 31.25% in the temperature subtopic and 26.56% in the surface-area subtopic. These findings highlight that low representational ability is directly associated with high levels of misconceptions. The study recommends strengthening representation-based learning and employing continuous diagnostic assessment to improve students’ conceptual structures.